The Economic Effects of the Consumer Over-Indebtedness Legislation in Italy: An Agent-Based Model - Luigi Bonaventura; Margherita Lazzara (International Journal of Business and Social Science Research, 2022)
Consumer over-indebtedness is a growing phenomenon in EU countries. Legislation addressing debt solutions for consumers does not have a long tradition in Italy. In 2012 Italy defined debt settlement procedures to reduce the impact of over-indebtedness. We build a disequilibrium agent-based model (abm), populated by heterogeneous consumers who behave according to boundedly rational behavioral rules. Through abm model, it will be possible to test the effects of this regulatory framework on the credit market, wealth distribution, and savings. In particular, the probability by means the local Tribunal accepts the consumer plan has an important role to balance between the need to provide an appropriate solution for enabling over-indebted individuals to start over with their lives, on one hand, and economic efficiency that debts should be paid.